A dayside plasma depletion observed at midlatitudes during quiet geomagnetic conditions. Issue 4 (21st February 2015) - Park, Jaeheung; Stolle, Claudia; Xiong, Chao; Lühr, Hermann; Pfaff, Robert F.; Buchert, Stephan; Martinis, Carlos R.
Abstract In this study we investigate a dayside, midlatitude plasma depletion (DMLPD) encountered on 22 May 2014 by the Swarm and GRACE satellites, as well as ground‐based instruments. The DMLPD was observed near Puerto Rico by Swarm near 10 LT under quiet geomagnetic conditions at altitudes of 475–520 km and magnetic latitudes of ∼25°–30°. The DMLPD was also revealed in total electron content observations by the Saint Croix station and by the GRACE satellites (430 km) near 16 LT and near the same geographic location. The unique Swarm constellation enables the horizontal tilt of the DMLPD to be measured (35° clockwise from the geomagnetic east‐west direction). Ground‐based airglow images at Arecibo showed no evidence for plasma density depletions during the night prior to this dayside event. The C/NOFS equatorial satellite showed evidence for very modest plasma density depletions that had rotated into the morningside from nightside. However, the equatorial depletions do not appear related to the DMLPD, for which the magnetic apex height is about 2500 km. The origins of the DMLPD are unknown, but may be related to gravity waves.